Hubungan Kualitas Pelayanan Keperawatan dengan Kepuasan Pasien Rawat Inap Kelas III di RSUD Pasar Minggu Jakarta Selatan - Rahayu, Sri (Jurnal Kesehatan Rajawali, 2024)
Hospital service quality metrics are controlled by two components: namely compliance with applicable quality standards as determined by law, and evaluation of service as perceived by patients. Providing services aimed at meeting patient needs is the obligation of health facilities, and hospitals are especially responsible for this. This research aims to gain an understanding of the relationship between the level of satisfaction experienced by third-class inpatients at Pasar Minggu Hospital, South Jakarta and the quality of nursing services provided. This research uses a quantitative methodology that takes a cross-sectional approach to data collection. Through the use of the total sampling method, the sample for this research was ninety people who were hospitalized at Pasar Minggu Regional Hospital in the third-class category. Univariate-bivariate analysis was carried out as part of the investigation in this study. Based on the findings, it is known that 86 people (95.6%) had good service quality, while only four people (4.4%) had poor service quality. Apart from that, 85 people (94.6%) had a good level of patient satisfaction, while five people (5.4%) had a poor level of satisfaction. The results of statistical analysis show that there is a relationship between the quality of nursing services and the level of satisfaction experienced by patients, with a p-value <0.05 (0.000). Therefore, every health service institution needs to ensure the maintenance of the quality of nursing services without differentiating between the classes of inpatients.